Development of Test Instruments Based on Cognitive Processes and Knowledge Dimensions on Environmental Chemistry - Sandra Sukmaning Adji; Rif’at Shafwatul Anam; Dodi Sukmayadi (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to develop an instrument that can measure the achievement of student learning outcomes in chemistry education in Environmental Chemistry courses, which refers to Bloom's Taxonomy, which has been revised along with the dimensions of knowledge from Anderson & Krathwohl. The research method used in this research is research and development with 4 (four) stages of research 1) define; 2) design; 3) develop; and 4) dissemination. The validation of this instrument was carried out by two experts in the field of chemistry and tested on 20 students. The instrument used is in the form of a description that takes the cognitive domains C1 to C3. In addition, in the instrument there are also 4 (four) dimensions of knowledge tested, namely factual, conceptual, procedural, and metacognitive. Based on the results of expert validation, it was found that in content there were no problems only in the use of verbs in the instrument requiring more operational verbs and based on the test results it was found that all the questions given showed that 30.15% of the questions were categorized as easy, 44, 80% were categorized as moderate and 25.05% were categorized as difficult. This study shows that the knowledge dimension in Bloom's taxonomy needs to be applied by considering the knowledge dimension to develop thinking skills in students.